Root ball plant and Ecological effects according to Hypothesis theory - Prabpram, Thiraya; Sirisomboonwech, Somchai; Klaisuban, Prapot; Muenphawong, Suntreeya (Journal for Developing the Social and Community, 2023)
Root ball plant is a tree used in landscapers' gardens and is the use of trees that are in the fields or are brought from planting plots that have bred various types of dugout trees for specific landscaping work. But at the same time Removing trees from their original sources to live in a changing environment Those trees may thrive or die due to digging, removal, or replanting in changing environmental conditions, and removing the trees from the original source also changes the original environment. This is in line with the Rivet Hypothesis theory that when trees are constantly removed from their original sources, the environment changes. The ecosystem will gradually change without the human being aware When it changes to the end, the ecosystem will be permanently changed. Like a rivet nut of an airplane that slowly slips out of an airplane until it finally crashes.